A Review of Another Gospel: Christian Nationalism and the Crisis of Evangelical Identity - Smith, Miles, IV (Christian scholar's review, 2025)
Another Gospel: Christian Nationalism and the Crisis of Evangelical Identity. Joel Looper. Published by Eerdmans in 2025. 168 pp. $ 19.99. 9780802884275. Amazon Goodreads.